2009
DOI: 10.1007/s11214-009-9506-9
|View full text |Cite
|
Sign up to set email alerts
|

Heating Diagnostics with MHD Waves

Abstract: Taroyan, Y., Erd?lyi, R. (2009). Heating Diagnostics with MHD Waves. Space Science Reviews, 149 (1-4), 229-254.The heating of the solar atmosphere is a fundamental problem of modern solar and astrophysics. A review of the seismological aspects of magnetohydrodynamic (MHD) waves with an emphasis on standing longitudinal waves in the context of coronal heating is presented. Efforts made recently may be split into two categories: forward modelling and data inversion. Forward modelling can be applied to predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 122 publications
0
64
0
Order By: Relevance
“…A recent study by Antolin & Shibata [40] investigates heating based on torsional Alfvén waves and suggests that, within the constraints of their 1.5 D model, this mechanism is viable only in a rather narrow regime, requiring long and thick loops (see Jess et al [41] for a possible observational identification of torsional Alfvén waves in the solar chromosphere). We refer the interested reader to Taroyan & Erdélyi [42] for a review of heating diagnostics with MHD waves.…”
Section: Acoustic and Magnetohydrodynamic Wavesmentioning
confidence: 99%
“…A recent study by Antolin & Shibata [40] investigates heating based on torsional Alfvén waves and suggests that, within the constraints of their 1.5 D model, this mechanism is viable only in a rather narrow regime, requiring long and thick loops (see Jess et al [41] for a possible observational identification of torsional Alfvén waves in the solar chromosphere). We refer the interested reader to Taroyan & Erdélyi [42] for a review of heating diagnostics with MHD waves.…”
Section: Acoustic and Magnetohydrodynamic Wavesmentioning
confidence: 99%
“…The highly dynamic solar photosphere is a rich source of waves, which are believed to be one of the plausible candidates responsible for heating the upper solar atmosphere (see a recent review by Taroyan & Erdélyi 2009, in this context). Magnetic fields and magnetohydrodynamic (MHD) waves play an important role in the solar atmosphere's energy budget.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of recently reported observed ubiquitous wave motions in a range of magCorrespondence to: V. Fedun (v.fedun@sheffield.ac.uk) netic field configurations in the photosphere, chromosphere and corona are of particular interest, since through different mechanisms of wave damping they might be responsible for the heating of the solar plasma (see e.g. Banerjee et al, 2007;Taroyan and Erdélyi, 2009). Furthermore, one can exploit these waves by the technique of solar magneto-seismology to probe the fine structure of the Sun's magnetised and highly dynamic atmosphere (see e.g.…”
Section: Introductionmentioning
confidence: 99%